2009
DOI: 10.1901/jaba.2009.42-641
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis and Treatment of Multiply Controlled Inappropriate Mealtime Behavior

Abstract: Functional analyses identified children whose inappropriate mealtime behavior was maintained by escape and adult attention. Function-based extinction procedures were tested individually and in combination. Attention extinction alone did not result in decreases in inappropriate mealtime behavior or a significant increase in acceptance. By contrast, escape extinction alone resulted in a decrease in inappropriate mealtime behavior and an increase in acceptance. However, inappropriate mealtime behavior did not dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
107
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 14 publications
6
107
0
Order By: Relevance
“…Although therapist effects may not be uncommon, these effects should be observed irrespective of condition and are not unique to the delivery of demands (e.g., English & Anderson, 2004;Huete & Kurtz, 2010). In addition, immediate responding during the escape condition has been observed when escape from demands is the only implicated function (e.g., Anderson & Long, 2002;Bachmeyer et al, 2009;DeLeon, Neidert, Anders, & Rodriguez-Carter, 2001). In addition, immediate responding during the escape condition has been observed when escape from demands is the only implicated function (e.g., Anderson & Long, 2002;Bachmeyer et al, 2009;DeLeon, Neidert, Anders, & Rodriguez-Carter, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although therapist effects may not be uncommon, these effects should be observed irrespective of condition and are not unique to the delivery of demands (e.g., English & Anderson, 2004;Huete & Kurtz, 2010). In addition, immediate responding during the escape condition has been observed when escape from demands is the only implicated function (e.g., Anderson & Long, 2002;Bachmeyer et al, 2009;DeLeon, Neidert, Anders, & Rodriguez-Carter, 2001). In addition, immediate responding during the escape condition has been observed when escape from demands is the only implicated function (e.g., Anderson & Long, 2002;Bachmeyer et al, 2009;DeLeon, Neidert, Anders, & Rodriguez-Carter, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Expulsion further decreased when feeders used the Nuk brush to present bites initially. Bachmeyer et al (2009) used escape extinction (nonremoval of the spoon) and attention extinction (no differential consequence for inappropriate mealtime behavior) individually and in combination with 4 children whose inappropriate mealtime behavior was maintained by escape and attention. Attention extinction alone did not decrease inappropriate mealtime behavior or increase acceptance.…”
mentioning
confidence: 99%
“…Studies have shown that behavioral interventions are effective as treatments for selective eating (e.g., Ahearn, 2001; Bachmeyer et al, 2009; Najdowski, Wallace, Doney, & Ghezzi, 2003; Piazza et al, 2002). For instance, Najdowski et al used differential reinforcement of alternative behavior (DRA), escape extinction, and stimulus fading to increase food acceptance of a young boy with autism in two settings.…”
mentioning
confidence: 99%